Analisis Pola Asuh Grandparenting dalam Pembentukan Karakter Anak Usia Dini di TK Islam Mujahidin Surakarta - Desie Dina Fitria; Sri Ernawati; Dhian Riskiana (Pusat Riset dan Inovasi Nasional, 2026)
Grandparenting is the act of raising children by grandparents as a form of implementing responsibilities as substitute parents. This care is transferred by grandparents due to factors such as parents being actively involved in work, divorce, or death. The parenting patterns they apply directly influence the development of children's character, such as discipline, responsibility, and independence. The purpose of this study is to understand how grandparenting parenting patterns are implemented and their impact on the formation of children's character, so that it can be a reference in improving the quality of intergenerational parenting and supporting child development. The research method used was interviews. Informants were 5 grandparents as the main respondents and 2 teachers as supporting respondents. The results obtained from the implementation of this study are in the form of parenting patterns implemented by grandparents provide an important contribution to the development of children's character such as discipline, responsibility, and independence.